2017
DOI: 10.3341/kjo.2016.0034
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Lymphangioma: Characteristics and Treatment Outcomes of 12 Cases

Abstract: PurposeTo report the patient characteristics and treatment outcomes in 12 cases of orbital lymphangioma.MethodsIn this study, orbital lymphangioma was diagnosed based on clinical, radiologic (computed tomography, magnetic resonance imaging), and histologic findings when possible. Patients whose vision was not compromised by orbital lymphangioma, or that did not have increased intraocular pressure (IOP), received oral corticosteroids. Orbital lymphangioma that affected vision or increased IOP was treated by sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…in their study, 85% of patients had proptosis; 73% had ptosis; and 46% had reduced ocular motility. Woo et al [4] reported that two out of 12 patients were aged 1 year; and all patients had proptosis and limited ocular motility at presentation. Our patient was a 14 months old boy who was brought to the eye clinic with acute proptosis of two days duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in their study, 85% of patients had proptosis; 73% had ptosis; and 46% had reduced ocular motility. Woo et al [4] reported that two out of 12 patients were aged 1 year; and all patients had proptosis and limited ocular motility at presentation. Our patient was a 14 months old boy who was brought to the eye clinic with acute proptosis of two days duration.…”
Section: Discussionmentioning
confidence: 99%
“…It is congenital and slowgrowing, consisting 0.3 to 1.5% of all orbital tumours [1]. It can present with spontaneous , orbital cellulitis [3] and proptosis [4]. In some of these patients proptosis may develop either slowly as the mass invades the orbit or suddenly during hemorrhage In childhood, the diagnosis is often made when proptosis occurs after bleeding as a result of minor trauma or upper respiratory infection, and may even occur spontaneously.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, massive hemorrhage may occur within the lymphangioma that may require urgent surgical intervention to decompress the orbit. [21] Indications for such an urgent surgical drainage include optic nerve compromise (suggested by appearance of relative afferent pupillary defect and/or deterioration of vision) or corneal exposure due to lagophthalmos. The acute presentation in such cases may often confuse the treating clinician who may misdiagnose it as a malignancy.…”
Section: Lymphangioma/combined Venous-lymphatic Vascular Malformationmentioning
confidence: 99%
“…However, orbital LVMs can extend to the frontotemporal region and the cheek and may be associated with intracranial vascular malformations, such as venous anomalies [ 8 , 9 , 10 ]. Lesions can be asymptomatic until they reach a large size, or intralesional hemorrhage occurs and causes swelling, proptosis, decreased motility of the eye, or pain [ 11 ]. Even though they are benign, these lesions can threaten vision by causing a compressive optic neuropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%